2011
DOI: 10.3945/jn.110.135954
|View full text |Cite
|
Sign up to set email alerts
|

Glycine-N Methyltransferase Expression in HepG2 Cells Is Involved in Methyl Group Homeostasis by Regulating Transmethylation Kinetics and DNA Methylation1,2

Abstract: Glycine-N methyltransferase (GNMT) is a potential tumor suppressor that is commonly inactivated in human hepatoma. We systematically investigated how GNMT regulates methyl group kinetics and global DNA methylation. HepG2 cells (GNMT inactive, GNMT-) and cells transfected with GNMT expressed vector (GNMT+) were cultured in low (10 μmol/L), adequate (100 μmol/L), or high (500 μmol/L) l-methionine, each with 2.27 μmol/L folate. Transmethylation kinetics were studied using stable isotopic tracers and GC-MS. Methyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
49
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(53 citation statements)
references
References 33 publications
4
49
0
Order By: Relevance
“…We recently discovered in vitro that GNMT expression does not exacerbate methyl group deficiency when the methionine supply is limited; instead it can protect cells from further hypomethylation induced by methionine depletion. Restoring GNMT expression in GNMT diminished cell lines is crucial in maintaining methyl group homeostasis via homocysteine transmethylation and transsulfuration kinetics (41). Adding to the current knowledge, results from the present study further demonstrated evidence that in GNMT-abundant tissue, that is, the liver, normal GNMT function is crucial for optimal folate status and hepatic-folatedependent biochemical reactions in vivo.…”
Section: Gnmt Expression Induced Folatedependent Homocysteine Remethysupporting
confidence: 58%
“…We recently discovered in vitro that GNMT expression does not exacerbate methyl group deficiency when the methionine supply is limited; instead it can protect cells from further hypomethylation induced by methionine depletion. Restoring GNMT expression in GNMT diminished cell lines is crucial in maintaining methyl group homeostasis via homocysteine transmethylation and transsulfuration kinetics (41). Adding to the current knowledge, results from the present study further demonstrated evidence that in GNMT-abundant tissue, that is, the liver, normal GNMT function is crucial for optimal folate status and hepatic-folatedependent biochemical reactions in vivo.…”
Section: Gnmt Expression Induced Folatedependent Homocysteine Remethysupporting
confidence: 58%
“…Glycine, as the precursor of sarcosine, induced cancer cell invasion [32]. Thus, the decreased glycine and sarcosine inhibited the tumor growth.…”
Section: Page 13 Of 27mentioning
confidence: 98%
“…As discussed above, the AR has important roles in regulating GNMT and the metabolism of sarcosine and the enzymes involved in the diversion of methyl groups into the transsulfuration and polyamine synthesis pathways. Increased GNMT expression leads to increased levels of the methyltransferase inhibitor SAH [200]. Therefore, changes in AR activity indirectly affect methyltransferase activity by modulating the SAM:SAH ratio.…”
Section: The Role Of Androgen Signaling On Methyltransferases and mentioning
confidence: 99%